2021
DOI: 10.1093/braincomms/fcab238
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent immunomodulatory effects of bortezomib in experimental autoimmune neuritis

Abstract: Proteasome inhibition with bortezomib has been reported to exert an immunomodulatory action in chronic autoimmune neuropathies. However, bortezomib used for the treatment of multiple myeloma induces a painful toxic polyneuropathy at a higher concentration. Therefore, we addressed this controversial effect and evaluated the neurotoxic and immunomodulatory mode of action of bortezomib in experimental autoimmune neuritis. Bortezomib-induced neuropathy was investigated in Lewis rats using the von Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…The involvement of the small nerve fibre and altered pain sensation was previously detected in the EAN by our group, 21 and we reproduced these results in our current experiments. Changed integrity of small nerve fibres is associated with nociception.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The involvement of the small nerve fibre and altered pain sensation was previously detected in the EAN by our group, 21 and we reproduced these results in our current experiments. Changed integrity of small nerve fibres is associated with nociception.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study from our group determined the involvement of small nerve fibres in the EAN by detecting alterations in nociception, more precisely, mechanical hyperalgesia over the disease course. 21 The performed Hargreaves and vF hair tests depicted an acute pain oversensitivity to mechanical and thermal stimuli, reaching its peak concordant with motor symptoms on Day 15 p.i. (Hargreaves test: P -value < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the positive and negative sensory deficits displayed in GBS and EAN, Wei et al [ 16 ] found compelling evidence that kinesin-5 inhibition reversed pathological pain by inhibiting vanilloid receptor subtype 1 (VR1) axonal trafficking. Painful sensory deficits also occur during autoimmune neuritis, indicating another possible potential indication for monastrol [ 60 ]. This warrants further investigations, which should not only include a thoroughly motor behavioural testing, but also testing of the sensory function for pain, temperature and touch.…”
Section: Discussionmentioning
confidence: 99%
“…The propensity for neuropathy is diminished by restricting the dose to a single cycle of bortezomib which appears sufficient to induce remission in immunological diseases and by adopting subcutaneous rather than intravenous route of administration. 92 …”
Section: B Cell Depleting Therapiesmentioning
confidence: 99%